2018
DOI: 10.1136/bmjopen-2017-021329
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sociodemographic factors and selection into UK postgraduate medical training programmes: a national cohort study

Abstract: IntroductionKnowledge about allocation of doctors into postgraduate training programmes is essential in terms of workforce planning, transparency and equity issues. However, this is a rarely examined topic. To address this gap in the literature, the current study examines the relationships between applicants’ sociodemographic characteristics and outcomes on the UK Foundation Training selection process.MethodsA longitudinal, cohort study of trainees who applied for the first stage of UK postgraduate medical tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 34 publications
(18 reference statements)
0
28
0
Order By: Relevance
“…Our results could be interpreted as students who come from non-traditional backgrounds tending to perform less well, have significantly lower Foundation Programme selection scores (as evidenced by our findings), and not applying for certain specialties as they do not believe they can compete for a training post with those who performed better on the UKFP 32. However, the weaker performance of non-traditional students on Foundation Programme selection may be due to financial rather than ability differences.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Our results could be interpreted as students who come from non-traditional backgrounds tending to perform less well, have significantly lower Foundation Programme selection scores (as evidenced by our findings), and not applying for certain specialties as they do not believe they can compete for a training post with those who performed better on the UKFP 32. However, the weaker performance of non-traditional students on Foundation Programme selection may be due to financial rather than ability differences.…”
Section: Discussionmentioning
confidence: 46%
“…However, we must also acknowledge some potential limitations of the study. First, in our previous research on selection into postgraduate (F2) training we reported how some of the contextual markers included in the analysis overlap, particularly socioeconomic class, ethnicity and place of medical qualification 32. We believe that these have a similar effect on specialty choice given the links between place, poverty and ethnicity in the UK 68 69.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this group has its own inherent biases. For example, most doctors in the UK are from more affluent or professional family backgrounds, and there is recent evidence that socio‐economic background is associated with specialty choice in the UK 80 . Unfortunately, we did not have details of respondents' socio‐economic background or insight into any other factors, which may have influenced their preferences (eg, amount of debt) so could not examine these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows, for example, strong connections between admission decisions by medical schools and the choices made by FY2 doctors about both specialty and place of work 78…”
mentioning
confidence: 99%